Relationship between standardized uptake value on 18F-FDG PET and PD-L1 expression in clear cell renal cell carcinoma - Liu, Ying; Huo, Yanlei; Ma, Chao; Lv, Zhongwei (Frontiers in Oncology, 2022)
Purpose: Recent evidence suggests that partial CCRCC may be susceptible to treatment with immune checkpoint inhibitors that target the PD-1/PD-L1 pathway. Evaluation of PD-L1 expression by non-invasive imaging is useful for the selection of immunotherapy-sensitive patients. It is currently unknown whether there is a relationship between 18F-FDG uptake and expression of PD-L1 in CCRCC. The purpose of the present study was to evaluate the utility of FDG-PET imaging to infer PD-L1 expression in CCRCC. Methods: PD-L1 expression was evaluated by immunohistochemistry (IHC) in tumor samples from a retrospective cohort of 58 patients with CCRCC who also underwent 18F-FDG PET/CT imaging. PD-L1 IHC scores were compared with FDG SUVmax, and SUVmean values, with CCRCC clinical characteristics and with IHC scores for glucose metabolism-related enzymes, GLUT1, HK2, LDHA and tumor suppressor gene VHL. Results: Higher PD-L1 expression significantly correlated with increased SUVmax, SUVmean, Tumor size, Lymph node metastasis and renal venous invasion (P <0.05). PD-L1 IHC scores positively correlated with LDHA and VHL expression IHC scores (P = 0.035, P = 0.011, respectively). Multivariate analysis revealed that the SUVmean and the lymph node metastasis correlated significantly with PD-L1 expression. Combined SUVmean and lymph node metastasis to predict low, medium, and high expressing tumors of PD-L1 was 20.59%, 29.41%, and 71.43%, respectively. Conclusion: The status of lymph node metastasis and SUVmean of the primary lesion were correlated with the expression of PD-L1 in CCRCC. Combined lymph node metastasis status and SUVmax can be used to predict PD-L1 expression and will be useful to monitor tumor response to immunotherapy.